CRIAÇÃO DE APLICATIVO PARA PREVENÇÃO DA SÍFILIS CONGÊNITA NA ATENÇÃO PRIMÁRIA À SAÚDE - Souza, Andreza Cossettin de (2023)
Congenital syphilis is the second leading cause of preventable fetal death worldwide, a fact that implies the seek for knowledge on this patology by healthcare professionals, aiming to extend this knowledge for society, as it becomes a worrying and fundamental issue regarding the prevention of this health problem. So, the development of an educational technological product on Congenital Syphilis, for nurses who work on the Primary Health Care and for the expectant mothers, aims to attend the needs and particularities of both groups. Objectives: To develop an application for expectant mothers and healthcare professionals as a strategy for health awareness towards the prevention of congenital syphilis at the Primary Health Care, as well as to validate the application’s design and content towards its functionallity for its purpose. Methodology: The Application aimed to contribute with the health education process on the Primary Heath Care for Congenital Syphilis prevention was developed on Dart Language, oriented by the Flutter Framework, a multiplataform application for Android and Iphone OperatingSystem (IOS) devices. Aiming to validate the product, which covered the second objective of this research, a methodological research was carried out to evaluate its content and design. The Content Validity Index (CVI) was calculated by three mathematical equations, the Scale-level content validity index based on the average method (S CVI/Ave), The proportion of items on an instrument that achieved a rating of 3 or 4 by all the content experts( S-CVI/UA) and the (CVI) Results: Syphilis is a disease that affects and worries thousands of people, healthcare professionals and managers. For this reason, the development of technologies is a strategy/tool that will allow women and her family’s self-awareness. Besides, compulsory notification is fundamental, in view of the fact that, whencarried out properly, it provides subsidies and information for other health sectors. It is expected that this application, combined with other methodologies, products and processes, will contribute to reducing the number of cases of gestational syphilis and congenital syphilis, as well as preventing infection and reinfection in women. Final Considerations: The instrument validation process, as in the APS-Previne Sífilis (APS-Syphilis Prevention), evinces the importance of this technology in the context of Primary Health Care. Poduct and Applicability: An impact is expected in medium and long term, by the use of this application on services and through the health education process enhancing the reduction of congenital syphilis. This production will contribute to work strategies and methodology, enabling it to be used in other scenarios that are similar to the one that will be implemented, due to its potential for replicability and potential for innovation.